(untitled) (LACCEI, 2024)
The objective of the present investigation was to carry out a systematic search for information about the technological advancement of equipment for the comminution of minerals. The study methodology was descriptive supported by the bibliographic review of the information. Therefore, it was concluded that the crushing stage involves equipment that breaks and reduces the volume of the rock through vibratory movements, in order to obtain a finer material, it should be noted that in recent decades equipment has been manufactured that consumes less energy and enable higher production at lower cost such as the Lokotrack LT200HP mobile cone crusher, the MKIII, the MX Multi-Action cone crushers and the NextGen crusher. On the other hand, in the grinding stage the reduction of the material is greater and is carried out using mills or rotating equipment in two ways: SAG grinding and conventional grinding, however, today there are new technologies in mills such as HIGmill™ which has 10% less energy savings compared to IsaMill™, multi-shaft mill which can reduce ore from F80 = 25mm to P80 = 300 microns and Hicom mills which are applied for fine and ultrafine micron grinding.